The Limnohabitans Genus Harbors Generalistic and Opportunistic Subtypes: Evidence from Spatiotemporal Succession in a Canyon-Shaped Reservoir - Jezberová, Jitka; Jezbera, Jan; Znachor, Petr; Nedoma, Jiří; Kasalický, Vojtěch; Šimek, Karel (Applied and environmental microbiology, 2017)
We studied the diversity of Limnohabitans using reverse line blot hybridization with Limnohabitans lineage-specific probes in the freshwater canyon-shaped Římov reservoir (Czech Republic). To examine the succession of distinct lineages, we performed (i) a study of an intensive spring sampling program at the lacustrine part of the Římov reservoir (from ice melt through a phytoplankton peak to the clear-water phase), and (ii) a seasonal study (April to November) when the occurrence of distinct Limnohabitans lineages was related to the inherent longitudinal heterogeneity of the reservoir. Significant spatiotemporal changes in the compositions of distinct Limnohabitans lineages allowed for the identification of "generalists" that were always present throughout the whole season as well as "specialists" that appeared in the reservoir only for limited periods of time or irregularly. Our results indicate that some phytoplankton groups, such as cryptophytes or cyanobacteria, and zooplankton composition were the major factors modulating the distribution and dynamics of distinct Limnohabitans lineages. The highest Limnohabitans diversity was observed during the spring algal bloom, whereas the lowest was during the summer cyanobacterial bloom. The microdiversity also markedly increased upstream in the reservoir, being highest at the inflow, and thus likely reflecting strong influences of the watershed.IMPORTANCE The genus Limnohabitans is a typical freshwater bacterioplankton and is believed to play a significant role in inland freshwater habitats. This work is unique in detecting and tracing different closely related lineages of this bacterial genus in its natural conditions using the semiquantitative reverse line blot hybridization method and in discovering the factors influencing the microdiversity, subtype alternations, and seasonality.
Keywords: Phytoplankton; subtypes; Cyanobacteria; bacterial diversity; Seasons; sinice; Comamonadaceae; Limnohabitans; reverse line blot hybridization; roční období; Fresh Water; Cryptophyta; Eutrophication; sladká voda; Czech Republic; eutrofizace; ekosystém; Česká republika; Ecosystem; fytoplankton; ITS; canyon-shaped freshwater reservoir